SCAI clinical expert consensus statement on the classification of cardiogenic shock: This document was endorsed by the American College of Cardiology (ACC), the American Heart Association (AHA), the Society of Critical Care Medicine (SCCM), and the Society of Thoracic Surgeons (STS) in April 2019. Issue 1 (19th May 2019) - Baran, David A.; Grines, Cindy L.; Bailey, Steven; Burkhoff, Daniel; Hall, Shelley A.; Henry, Timothy D.; Hollenberg, Steven M.; Kapur, Navin K.; O'Neill, William; Ornato, Joseph P.; Stelling, Kelly; Thiele, Holger; et al.
Abstract: Background: The outcome of cardiogenic shock complicating myocardial infarction has not appreciably changed in the last 30 years despite the development of various percutaneous mechanical circulatory support options. It is clear that there are varying degrees of cardiogenic shock but there is no robust classification scheme to categorize this disease state. Methods: A multidisciplinary group of experts convened by the Society for Cardiovascular Angiography and Interventions was assembled to derive a proposed classification schema for cardiogenic shock. Representatives from cardiology (interventional, advanced heart failure, noninvasive), emergency medicine, critical care, and cardiac nursing all collaborated to develop the proposed schema. Results: A system describing stages of cardiogenic shock from A to E was developed. Stage A is "at risk" for cardiogenic shock, stage B is "beginning" shock, stage C is "classic" cardiogenic shock, stage D is "deteriorating", and E is "extremis". The difference between stages B and C is the presence of hypoperfusion which is present in stages C and higher. Stage D implies that the initial set of interventions chosen have not restored stability and adequate perfusion despite at least 30 minutes of observation and stage E is the patient in extremis, highly unstable, often with cardiovascular collapse. Conclusion: This proposed classification system is simple, clinically applicable across the care spectrum from pre‐hospital providers to intensive care staff but will require future validation studies to assess its utility and potential prognostic implications.